Forensic Investigation of Drowning, Biochemical Markers and Diatom Testing for Confirming Cause of Death. A cross-sectional study - Ume Kalsoom Asiya Fazal Farhat Sultana, Wasiq Ahmed Mansoora Mirza, Muhammad Anwar Sibtain Fazli (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A cross-sectional forensic study evaluated the utility of biochemical markers (serum surfactant D,NT-proBNP, D-dimer) and diatom quantification for confirming drowning as the cause of death.Eighty postmortem cases were investigated